Bridges for pedestrians with random parameters using the stochastic finite elements analysis - Szafran, Jacek; Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The main aim of this paper is to present a Stochastic Finite Element Method analysis with reference to principal design parameters of bridges for pedestrians: eigenfrequency and deflection of bridge span. They are considered with respect to random thickness of plates in boxed-section bridge platform, Young modulus of structural steel and static load resulting from crowd of pedestrians.
Keywords: bridges for pedestrians; eigenfrequencies; Stochastic Finite Element Method; response function method; generalized stochastic perturbation technique; reliability analysis